Spectrophotometric Determination of Ni(II) in Industrial Samples After Separation By Adsorption of Its 1,4-Dihydroxyanthra-Quinone Complex on Microcrystalline Naphthalene - Bhajan Singh, Har; Kumar , Sudersana; Nadira Wasi, M.R.; Satake, Mastada (Asian Journal of Chemistry, 2010)
Nickel-1,4-dihydroxanthraquinorie (DHA) complex formed at pH 8.6 is adsorbed on microcrystalline naphthalene and subsequently dissolved in DMF. Absorbance of the complex at 560 nm is proportional to the concentration of Ni(II) in the range of 0.6–3.0 ppm. Ag(I), Hg(II) and Cd(II) do not interfere in 10-fold concentration but Co(II), Cu(II), Mn(II) and Zn(II) cause serious interference. The method has been successfully applied to determine nickel in hydrogenation catalyst, hydrogenated oils and electroplating bath solutions. Unlike Ni-DMG complex, the absorbance in case of Ni-1,4-DHA need not be recorded immediately as it remains constant with time.